2011
DOI: 10.1038/bmt.2011.64
|View full text |Cite
|
Sign up to set email alerts
|

Features of EBV reactivation after reduced intensity conditioning unrelated umbilical cord blood transplantation

Abstract: This single centre study assessed the incidence, kinetics and predictive factors of EBV reactivation and EBVrelated lymphoproliferative diseases (LPD) in 33 consecutive patients who received a reduced intensity conditioning (RIC) before umbilical cord blood transplantation (UCBT). During the first 6 months after UCBT, weekly all patients were DNA-PCR screened in the peripheral blood for EBV reactivation and were clinically monitored for clinical features attributable to EBV. The cumulative incidences of EBV re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 34 publications
0
10
0
2
Order By: Relevance
“…A recent French single-center study, including 33 UCBT only with RIC regimen, found an overall incidence of EBV reactivation about 5/33 (15%) and 2 EBV-PTLD. 8 Given our results, we could speculate that patients who underwent UCBT have a risk of EBV reactivation probably correlated to the circumstances of the graft in terms of conditioning and immunosuppression. Immaturity of UCB lymphocytes could have been responsible for higher susceptibility to EBV reactivation, as previously described for HHV6, 14 adenovirus 15 and VZV.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…A recent French single-center study, including 33 UCBT only with RIC regimen, found an overall incidence of EBV reactivation about 5/33 (15%) and 2 EBV-PTLD. 8 Given our results, we could speculate that patients who underwent UCBT have a risk of EBV reactivation probably correlated to the circumstances of the graft in terms of conditioning and immunosuppression. Immaturity of UCB lymphocytes could have been responsible for higher susceptibility to EBV reactivation, as previously described for HHV6, 14 adenovirus 15 and VZV.…”
Section: Discussionmentioning
confidence: 84%
“…5 The ability of cord blood-naive T cells to regulate EBV reactivation is uncertain, and the incidence of EBV viremia and EBV-PTLD have to be assessed in UCBT recipients. Three studies have been published on the subject, [6][7][8] and none of them performed systematic EBV RQ-PCR monitoring. The aim of this retrospective multicenter study was to investigate the incidence and risk factors of EBV events after UCBT.…”
Section: Introductionmentioning
confidence: 98%
“…Indeed, patients eligible to RIC/NMA allo-SCT are frequently elderly, heavily pretreated, or impaired by comorbidities, and most physicians hesitate to use UCB to perform RIC/NMA allo-SCT in them when there is no matched related or unrelated donor available. The main cause of NRM after UCB transplantation is infectious complications [23][24][25], but in our retrospective study, we were unable to analyze the impact of infection-related NRM. The cumulative incidence of grade III and IV aGVHD and cGVHD was lower in the UCB group compared with the MisMUD.…”
Section: Discussionmentioning
confidence: 88%
“…The reported incidence of EBV DNA-emia ranging between 0.1-63% is largely dependent on the type of transplant, assay sensitivity, defined level of DNA-emia, use of systematic screening and its timing. [18][19][20][21][22][23][24][25][26][27] In a recent EBMT study, the overall incidence of PTLD after allogeneic HSCT was 3.2%, varying from 1.2% in matched family donor (MFD) to 2.8% in mismatched family donor (haploidentical/MMFD), 4.0% in matched unrelated donor (MUD), and 11.2% in mismatched unrelated donor (MMUD) recipients. 3 In recipients of unrelated cord blood (CBT), the incidence of EBV-PTLD was 2.6-3.3% for myeloablative transplants, and 7-12.9% in nonmyeloablative transplants.…”
Section: Epidemiologymentioning
confidence: 99%